Precision Medicine for Advanced Pancreas Cancer: The Individualized Molecular Pancreatic Cancer Therapy (IMPaCT) Trial - Chantrill, Lorraine A; Nagrial, Adnan M; Watson, Clare; Johns, Amber L; Martyn-Smith, Mona; Simpson, Skye; Mead, Scott; Jones, Marc D; Samra, Jaswinder S; Gill, Anthony J; Watson, Nicole; Chin, Venessa T; et al. (Clinical cancer research, 2015)
Personalized medicine strategies using genomic profiling are particularly pertinent for pancreas cancer. The Individualized Molecular Pancreatic Cancer Therapy (IMPaCT) trial was initially designed to exploit results from genome sequencing of pancreatic cancer under the auspices of the International Cancer Genome Consortium (ICGC) in Australia. Sequencing revealed small subsets of patients with aberrations in their tumor genome that could be targeted with currently available therapies. The pilot stage of the IMPaCT trial assessed the feasibility of acquiring suitable tumor specimens for molecular analysis and returning high-quality actionable genomic data within a clinically acceptable timeframe. We screened for three molecular targets: HER2 amplification; KRAS wild-type; and mutations in DNA damage repair pathways (BRCA1, BRCA2, PALB2, ATM). Tumor biopsy and archived tumor samples were collected from 93 patients and 76 were screened. To date 22 candidate cases have been identified: 14 KRAS wild-type, 5 cases of HER2 amplification, 2 mutations in BRCA2, and 1 ATM mutation. Median time from consent to the return of validated results was 21.5 days. An inability to obtain a biopsy or insufficient tumor content in the available specimen were common reasons for patient exclusion from molecular analysis while deteriorating performance status prohibited a number of patients from proceeding in the study. Documenting the feasibility of acquiring and screening biospecimens for actionable molecular targets in real time will aid other groups embarking on similar trials. Key elements include the need to better prescreen patients, screen more patients, and offer more attractive clinical trial options.